Nonanalytic solutions of the KdV equation. (17th May 2004) - Byers, Peter; Himonas, A. Alexandrou
Abstract : We construct nonanalytic solutions to the initial value problem for the KdV equation with analytic initial data in both the periodic and the nonperiodic cases.